Occult blood in feces is associated with a poor functional outcome of ischemic stroke patients receiving intravenous thrombolysis - Peng, Min; Sun, Xiaoyun; Yuan, Xiangling; Tao, Chenjuan; Xu, Gelin (Frontiers in Neurology, 2025)
BackgroundAlthough fecal occult hemoglobin is commonly valued as a screening tool for colorectal cancer, few studies have examined the clinical significance of fecal immunochemical testing (FIT) in other diseases. This study aimed to explore the association between occult blood in feces and functional outcomes of acute ischemic stroke (AIS) patients who received intravenous thrombolysis treatment.MethodsPatients diagnosed with acute ischemic stroke and received thrombolytic therapy were recruited from the neurology department of the Affiliated Hospital of Hangzhou Normal University. FIT was conducted for patients during hospitalization. Functional outcome was assessed by the modified Rankin Scale (mRS). A favorable outcome was defined as mRS 0–2 and a poor outcome as mRS 3–6.ResultsA total of 214 patients were included for analysis. The proportion of FIT-positive patients was higher in the poor outcome group than in the favorable group (12.3% vs. 45.6%, p < 0.001). Logistic regression models showed that FIT-positive patients had an increased risk of a poor outcome (OR: 4.188, 95% CI: 1.424–11.51, p = 0.005) after adjusting for possible variables. Moreover, in addition to gastrointestinal bleeding, NIHSS score at baseline (OR: 1.092, 95% CI: 1.013–1.176, p = 0.021) and white blood cell level (OR: 1.215, 95% CI: 1.018–1.448, p = 0.031) were also the independent risk factors for positive FIT after thrombolytic therapy in AIS.ConclusionPositive FIT was related to the poor outcomes in AIS patients who received thrombolytic therapy. High NIHSS scores at baseline and high white blood cell levels were the risks of FIT.